2011
DOI: 10.1007/s00234-010-0833-z
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of peripheral nerve in patients with chronic inflammatory demyelinating polyradiculoneuropathy: a feasibility study

Abstract: Our preliminary data suggest that the noninvasive DTI assessment of peripheral nerves may provide useful information in patients with CIDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 22 publications
10
68
0
2
Order By: Relevance
“…Previous studies have consistently demonstrated that DTI derived FA in rodent22, 43, 44 and human peripheral nerves is a valid measure for axonal injury 17, 21, 23…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies have consistently demonstrated that DTI derived FA in rodent22, 43, 44 and human peripheral nerves is a valid measure for axonal injury 17, 21, 23…”
Section: Discussionmentioning
confidence: 87%
“…This method is useful to provide anatomical data and to detect pathologies such as tumors that affect the continuity of nerves 18, 19. More recently, diffusion tensor imaging of peripheral nerves has been introduced as a tool to quantify nerve damage and regeneration 20, 21, 22…”
Section: Introductionmentioning
confidence: 99%
“…DTI has mainly been applied to the functional analysis and diagnosis of diseases in the central nervous system. Recently, this technique has also been applied to several peripheral nerves, namely the median nerve, 12 tibial nerve 13,14 and lumbar plexus. 15 Those studies demonstrated that the ADC and FA could reflect the pathological conditions of peripheral nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Nerve pathology can also be probed directly via quantitative MRI techniques. For example, diffusion MRI of peripheral nerves yields metrics that relate to disability 18,19 ; however, this method often requires longer, lower resolution acquisitions than desired. Similar to diffusion MRI, magnetization transfer ratio (MTR) imaging is sensitive to changes in myelin density that can occur from demyelination or axonal loss, 20 and fast, high-resolution MTR imaging of peripheral nerves is feasible.…”
mentioning
confidence: 99%